Binding Stoichiometry of a Recombinant Selenophosphate Synthetase with One Synonymic Substitution E197D to a Fluorescent Nucleotide Analog of ATP, TNP-ATP. (30th January 2013) - Preobrazhenskaya, Y. V.; Stenko, A. I.; Shvarts, M. V.; Lugovtsev, V. Y.
Abstract : The transformation of the strain DH 5 α TM -T1 R with plasmid vector pET11a containing the cloned gene of bacterial selenophosphate synthetase (SPS), selD, from the E. coli BL21-Gold (DE3) strain gives an overproducing strain of SPS with one synonymic substitution, E197D. The transformation efficiency was estimated as 8 × 10 8 CFU/ μ g plasmid DNA. 28 mg of highly purified preparation of recombinant SPS capable of binding TNP-ATP was eluted from DEAE-Sephadex column in amount of 15 % from the total soluble protein in crude extract. The fluorescent derivative of ATP, 2′(3′)- O -(2, 4, 6-trinitrophenyl)adenosine-5′-triphosphate (TNP-ATP), was used as a synthetic analog of the substrate for the monitoring and quantitative analysis of the functional activity of SPS. The non-linear regression analysis of the saturation curve of TNP-ATP binding to D197 SPS with GraphPad Prism software fits to a model with 2 distinct binding sites with K D s different in order. The SPS existence in a form of tetramer in given reaction conditions, in accordance with the concentration stoichiometry of 4 moles of TNP-ATP to 1 mole of recombinant protein, is being discussed. The tetramer structure was predicted with molecular modelling software YASARA and modelled in vacuum using steepest descent minimization energy method. We hypothesize here the recombinant SPS exists as a dimer in solution with two active sites capable of ATP binding in each subunit.